Flow Rate Sensor Design And Development (Flux) - Mohamed Zain, Khairu Anuar (Universiti Sains Malaysia, 2006)
Flow measurement is essential in many industries such as the oil, power, chemical, food, water, and waste treatment industries. These industries require the determination of the quantity of a fluid, either gas, liquid, or steam, that passes through a check point, either a closed conduit or an open channel, in their daily processing or operating. The quantity to be determined may be volume flow rate, mass flow rate, flow velocity, or other quantities related to the previous three. The instrument to conduct flow measurement is called flow meter. The development of a flow meter involves a wide variety of disciplines including the flow sensors, the sensor and fluid interactions through the use of computation techniques, the transducers and their associated signal processing units, and the assessment of the overall system under ideal, disturbed, harsh, or potentially explosive conditions in both the laboratory and the field. The purpose of this final year project is to design and developed a flow rate sensor system using flux characteristic. The scope of this project is to measure the flow rate of a clean tap water; witch is flowing through a pipe in a reasonable range of flow rate. Other types of fluid or moving mass are not taken into consideration when designing the sensor and system. Only the linear characteristic of the flow rate sensor are calculated. The designing processes begin with designing the electromagnetic induced circuit, after that and amplifier circuits will be design to amplifier the sensor output signal. An ADC circuits than are taken into considerations to convert the analog signal into digital signal, so that it could be process digitally using microprocessor circuits. All the circuits are combined